Resources and Praxeologies Involved in Teachers' Design of an Interdisciplinary STEAM Activity - Gabriella Pocalana; Ornella Robutti; Elena Ciartano (MDPI AG, 2024)
This study aimed to examine the collaborative design of an interdisciplinary STEAM activity conducted by lower-secondary school teachers of different disciplines. We adopted an approach based on a case study involving four teachers (art, music, technology, and mathematics/science teachers) designing an activity focused on the concept of symmetry. We gathered data through oral, semi-structured interviews with the teachers and through schematic representations of resource systems provided by the teachers themselves. Data analysis aimed to identify the different kinds of resources the teachers relied on, their utilization schemes, and the overarching meta-didactical praxeology adopted by the teachers for their collaborative design work. The theoretical model adopted for data analysis was a combination of the Documentational Approach to Didactics and the Meta-Didactical Transposition frameworks, originally introduced to study the work of researchers in the context of teacher professional development. An application of this model to the collaborative design work of teachers can provide a fresh insight into the relationship between teachers' documentation work for the design of a STEAM activity, the practices that they adopt to address this shared task (praxis), and the shared justifying discourses (logos) for their praxis.